Synthesis and Characteristics of Ag, Cu/Au Core/Shell Nanoparticles Produced by Pulse Laser Ablation - Ibrhim, Isam M. (Iraqi Journal of Science, 2021)
Colloidal dispersions of mono Au, Ag , Cu and bimetallic Ag/Au and Cu/Aucore/shell nanoparticles are synthesized by pulsed laser ablation of metals targetsimmersed in 5 ml distilled water (DW). Surface Plasmon resonance (SPR) andparticle sizes are characterized by UV-VIS and HRTEM, the X-ray diffractionshows the structure of core/shell. The Surface Plasmon resonance of the producednanoparticles solutions for silver nanoparticles about 402 nm and coppernanoparticles about 636 nm. While for the core-shell observed two peaks of SPR,Ag/Au core/shell at (406-516) nm, and Cu/Au core/shell observed one peak at565nm, because the region of gold and copper close together. The shape andparticle size have been confirmed by HRTEM measurement, average size is around12nm for Ag NPs, and 14nm for Cu NPs, while the average size is around 11nm forAg/Au core/shell NPs and around 13nm for Cu/Au core/shell NPs. Zeta potential(ZP) results proved the silver nanoparticle is more stabilizing (-23.11 mV) thanother noble metal nanoparticles,while Ag/Au core/shell is more stabilizing(-27.77mV) with comparison with Cu/Au core/shell which less stabilizing.